Design, Synthesis and Evaluation of AdSS Bisubstrate Inhibitors. (10th September 2020) - Tibrewal, Nidhi; Elliott, Gregory I.
Abstract: Many cancers lack the expression of methylthioadenosine phosphorylase (MTAP). These cancers require adenylosuccinate synthetase (AdSS) for nucleic acid synthesis. By inhibiting adenylosuccinate synthetase, we potentially have a new therapeutic agent. Bisubstrate inhibitors were synthesized and evaluated against purified AdSS. The best activity was obtained with adenosine bearing a four‐carbon linker that connects the N ‐formyl‐ N ‐hydroxy moiety to the 6‐position of the purine nucleoside. Abstract : Taking away the key : Compounds have been developed to bind in the aspartic acid and inosine monophosphate pocket of adenylosuccinate synthetase (AdSS), a key enzyme in cell proliferation. Inhibition of this enzyme affects purine biosynthesis and is expected to cause selective cell death in lung cancer. The bisubstrate strategy could be useful in designing highly specific inhibitors of AdSS.